2020
DOI: 10.1186/s12916-020-01743-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between childhood trauma and risk for obesity: a putative neurocognitive developmental pathway

Abstract: Background Childhood trauma increases the risk for adult obesity through multiple complex pathways, and the neural substrates are yet to be determined. Methods Participants from three population-based neuroimaging cohorts, including the IMAGEN cohort, the UK Biobank (UKB), and the Human Connectome Project (HCP), were recruited. Voxel-based morphometry analysis of both childhood trauma and body mass index (BMI) was performed in the longitudinal IMAGEN cohort; validation of the findings was performed in the UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Childhood maltreatment, which mainly includes physical, sexual and emotional abuse and neglect, is common worldwide with pediatric prevalence rates of 13-36% (Lim, Howells, Radua, & Rubia, 2020). These adverse early-life experiences involved bio-psycho-social mediators and moderators (Sideli et al, 2020), and have been suggested to be closely related with cognitive decline, attention impairment, emotional dysregulation, and reward anticipation disorder (Hart et al, 2018;Lim et al, 2016), and may even increase the risks of suffering from mental illness, such as posttraumatic stress disorder (PTSD) (Daniels, Lamke, Gaebler, Walter, and Scheel, 2013), major depressive disorder (MDD) (Goltermann et al 2022;Guo et al 2022;Haidl et al 2021), borderline personality disorder (Herzog, Kube, & Fassbinder, 2022), schizophrenia (Cancel, Dallel, Zine, El-Hage, & Fakra, 2019;D'Andrea et al, 2022;Sideli et al, 2020), substance abuse (Hughes et al, 2017), eating disorders (Cascino et al, 2022;Luo et al, 2020), as well as functional somatic and visceral pain syndromes (Chandan et al, 2020). Neurobiology changes of the brain might underlie the occurrence of the above symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood maltreatment, which mainly includes physical, sexual and emotional abuse and neglect, is common worldwide with pediatric prevalence rates of 13-36% (Lim, Howells, Radua, & Rubia, 2020). These adverse early-life experiences involved bio-psycho-social mediators and moderators (Sideli et al, 2020), and have been suggested to be closely related with cognitive decline, attention impairment, emotional dysregulation, and reward anticipation disorder (Hart et al, 2018;Lim et al, 2016), and may even increase the risks of suffering from mental illness, such as posttraumatic stress disorder (PTSD) (Daniels, Lamke, Gaebler, Walter, and Scheel, 2013), major depressive disorder (MDD) (Goltermann et al 2022;Guo et al 2022;Haidl et al 2021), borderline personality disorder (Herzog, Kube, & Fassbinder, 2022), schizophrenia (Cancel, Dallel, Zine, El-Hage, & Fakra, 2019;D'Andrea et al, 2022;Sideli et al, 2020), substance abuse (Hughes et al, 2017), eating disorders (Cascino et al, 2022;Luo et al, 2020), as well as functional somatic and visceral pain syndromes (Chandan et al, 2020). Neurobiology changes of the brain might underlie the occurrence of the above symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…2022; Haidl et al . 2021), borderline personality disorder (Herzog, Kube, & Fassbinder, 2022), schizophrenia (Cancel, Dallel, Zine, El-Hage, & Fakra, 2019; D'Andrea et al, 2022; Sideli et al, 2020), substance abuse (Hughes et al, 2017), eating disorders (Cascino et al, 2022; Luo et al, 2020), as well as functional somatic and visceral pain syndromes (Chandan et al, 2020). Neurobiology changes of the brain might underlie the occurrence of the above symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…An argument for keeping weight as a separate priority was that there are many causes for suboptimal weight and, among women with obesity, it is not simply a matter of poor nutrition or physical inactivity. For example, women with polycystic ovary syndrome 46 or depression, 47 people who experience food insecurity 48 and people who have experienced childhood trauma 49 are more likely to have a body mass index in overweight or obese categories. These issues can be interrelated and are not necessarily addressed with nutrition and physical activity alone.…”
Section: Discussionmentioning
confidence: 99%
“…At the voxel level, we used 1 http://www.fil.ion.ucl.ac.uk/spm/ 2 https://neuro-jena.github.io/software.html#tom a two-sided test with a significance level of α = 0.001, whereas at the cluster level, we used a permutation-based family-wise error correction with a significance level of α = 0.05. Significant GMVs were defined as clusters with more than 217 voxels that fell within the 90% confidence interval (CI) of the smoothing kernel voxels (24,25). An association analysis was then conducted between significant GMVs and clinical symptoms of autism and language development scores.…”
Section: Analysis Of Brain Volumes Structure Association Analysismentioning
confidence: 99%